PENGARUH MODEL OPEN ENDED TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA SMP - Noviyana, Hesti (JURNAL e-DuMath, 2018)
Abstract: The research problem is related to students mathematical problem solving ability and application of Open Ended model. The purpose of this research is to know the influence of Open Ended model on mathematical problem solving ability of grade VIII SMP students. Research using experimental method. Data analysis using parametric statistics. Research population of all students of grade VIII SMP Negeri 1 Candipuro Lampung Selatan, the sample is taken 2 classes, namely VIII A as experimental class and VIII C as a control class taken using Cluster Random Sampling technique. Mathematical problem solving ability is measured with essay test of 5 questions. Hypothesis testing uses t-test, with t value = 9,07. At significance level 5% known tdaf =Â  2.00 means thit > tdaf that is 9.07> 2.00, so it is concluded "There is influence of applying of Open Ended model to mathematical problem solving ability of student of class VIII Semester Even SMP Negeri 1 Candipuro Lampung Selatan Lesson Year 2017/2018 ". This situation is seen from the average grade of the experimental class students is 74.19 is greater than the control class which has an average value of 42.5.Keywords: Open ended, ability, math problem solving